2013
DOI: 10.1634/theoncologist.2012-0401
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Pediatric Oncology Patients From Influenza

Abstract: Influenza is a common respiratory pathogen. Its severity can be unpredictable, but people with chronic illness are at increased risk of severe infection, complications, and death from influenza. This review examines evidence to support various strategies to protect pediatric oncology patients from influenza-related morbidity. Influenza vaccination should be considered standard. Additional evidence-supported measures include antiviral treatment, antiviral prophylaxis, cohorting of patients, and hospital infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 99 publications
2
17
0
Order By: Relevance
“…A full dose of vaccine was also associated with a significantly greater magnitude of immunological response after (Table IV, P ¼ 0.04) and after two doses (Table V, P < 0.001), an association confirmed by performing ANOVA of repeated measures (probability > F < 0.0001). A similar "doseresponse effect has been reported in other contexts [16] and may represent a potential strategy to further improve immunogenicity of influenza vaccine in children with ALL. A potential confounder to this effect of dose on vaccine immunogenicity is the older age (!13 years) of the children receiving the adult dose of the vaccine.…”
Section: Discussionsupporting
confidence: 71%
“…A full dose of vaccine was also associated with a significantly greater magnitude of immunological response after (Table IV, P ¼ 0.04) and after two doses (Table V, P < 0.001), an association confirmed by performing ANOVA of repeated measures (probability > F < 0.0001). A similar "doseresponse effect has been reported in other contexts [16] and may represent a potential strategy to further improve immunogenicity of influenza vaccine in children with ALL. A potential confounder to this effect of dose on vaccine immunogenicity is the older age (!13 years) of the children receiving the adult dose of the vaccine.…”
Section: Discussionsupporting
confidence: 71%
“…A recent multicenter study of 115 patients with solid tumors who were infected with influenza A (H1N1) in 2009 found high rates of hospitalization (50%), pneumonia (23%), and death (9.5%) . Up to two‐thirds of children receiving cancer therapy who contract influenza are hospitalized, for 2 to 7 days on average, with respiratory complications such as pneumonia, respiratory failure, and a need for ventilator support in 10% to 20% of patients . In addition to influenza‐related morbidity, influenza infection in children can result in treatment delays averaging 3 weeks, potentially affecting long‐term prognosis .…”
Section: Selected Vaccines Important For Patients With Cancer and Surmentioning
confidence: 99%
“…Up to two‐thirds of children receiving cancer therapy who contract influenza are hospitalized, for 2 to 7 days on average, with respiratory complications such as pneumonia, respiratory failure, and a need for ventilator support in 10% to 20% of patients . In addition to influenza‐related morbidity, influenza infection in children can result in treatment delays averaging 3 weeks, potentially affecting long‐term prognosis . Vaccination of pediatric patients with cancer and family members is an important prevention strategy .…”
Section: Selected Vaccines Important For Patients With Cancer and Surmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients on RTX and those with active disease had a poorer response [50,51]. In studies in children with hematological malignancies, patients were found to have protective anti-influenza antibody rates of 30-70 % post-vaccination, with increases in the number and magnitude of the doses sometimes required for improved responses [52,53].…”
Section: Patients Receiving Steroidsmentioning
confidence: 99%